Garis Besar Ideal Demokrasi dalam Islam: Satu Tinjauan Ringkas - ahmad nabil amir; Tasnim Abdul Rahman (Jurnal Keamanan Nasional, 2025)
This study investigates th conceptual nexus between democracy and the principle of shura within the landscape of contemporary Islamic political thought. It aims to elucidate the compatibility of democratic mechanisms with Islamic axiology through an ethical-constitutional approach grounded in maqasid al-shari’ah (the higher objectives of Islamic law). Employing a qualitative descriptive-analytical methodology, the research applies Fazlur Rahman’s hermeneutical framework to critically examine the discourse of prominent intellectuals, specifically Rachid Ghannouchi, Ahmad Al-Raysuni, and Nurcholish Madjid. The findings indicate that, within this interpretive scope, democracy is not merely congruent with the principles of shura and justice, but serves as a vital instrument to fortify Islamic political aspirations for establishing egalitarian, participatory, and accountable governance. Consequently, this article proposes a novel synthesis between Shari’ah-based ethics and modern democratic praxis, offering significant implications for strengthening political architecture in democratizing Muslim nations.